Предмет: Алгебра,
автор: krivykhnikita
помогите сделать 8 пж
Приложения:
Zombynella:
Спасибо)
Ответы
Автор ответа:
1
Ответ:
В решении.
Объяснение:
(3х - 2х² - 3у + 2ху)/(у² - х²) =
= ((2ху - 2х²) - (3у - 3х))/((у - х)(у + х)) =
= (2х(у - х) - 3(у - х))/((у - х)(у + х)) =
= ((у - х)(2х - 3))/((у - х)(у + х)) =
сократить (у - х) и (у - х) на (у - х);
= (2х - 3)/(у + х).
Автор ответа:
0
Ответ:
вот
Объяснение:
думаю так . не знаю правильно или нет
Приложения:
Похожие вопросы
Предмет: Русский язык,
автор: ангелок031
Предмет: Русский язык,
автор: Кнопка25052002
Предмет: Русский язык,
автор: Аноним
Предмет: Математика,
автор: marinavik85